Cranial and lumbosacral hypertrophic pachymeningitis associated with systemic lupus erythematosus: A case report. Issue 39 (September 2016) - Han, Fei; Zhong, Ding-Rong; Hao, Hong-Lin; Kong, Wei-Ze; Zhu, Yi-Cheng; Guan, Hong-Zhi; Cui, Li-Ying
Abstract: Background: Hypertrophic pachymeningitis (HP) is a chronic disease characterized by inflammatory hypertrophy and fibrosis of dura mater. It can be divided into cranial and spinal forms depending on the location of the lesion. HP involving 2 separate sites simultaneously is quite uncommon. Case summary: This study presents a case of a 49-year-old woman with pathologically confirmed cranial and lumbosacral hypertrophic pachymeningitis associated with systemic lupus erythematosus (SLE), which is a rare etiology of HP. She experienced persistent numbness and pain of the left lower limb, followed by headache and seizures. In laboratory tests, levels of erythrocyte sedimentation rate and C-reactive protein were elevated, and antinuclear antibodies and anti–double-strand deoxyribonucleic acid (DNA) antibodies were detected. Magnetic resonance imaging revealed dural thickening with homogenous gadolinium enhancement both at lumbosacral level and over cerebral convexities. Histology suggested chronic inflammation in spinal dura mater with extensive fibrosis, dense lymphoplasmacytic infiltrate, and focal vasculitis. Treatment with corticosteroids and cyclophosphamide was started with significant clinical and radiological improvement. Conclusion: HP is etiologically heterogeneous. Despite its rarity, SLE should be considered in the differential diagnosis of HP. Early recognition and therapy may provide an optimal outcome.